A specific controlled ovarian stimulation (COS) protocol for fertility preservation in women with breast cancer undergoing neoadjuvant chemotherapy - Cavagna, Felipe [UNESP]; Pontes, Anagloria [UNESP]; Cavagna, Mario; Dzik, Artur; Donadio, Nilka F.; Portela, Rafael; Nagai, Michelle T.; Gebrim, Luiz H. (Termedia Sp. z.o.o., 2017)
Aim of the study: The authors present a novel and specific controlled ovarian stimulation protocol for fertility preservation in women with estrogen-positive receptor breast cancer undergoing neoadjuvant chemotherapy. The protocol foresees random start ovarian stimulation and the use of letrozole associated to tamoxifen. Material and methods: Forty breast cancer patients were included in the study. COS was performed either with recombinant FSH or hMG. Concomitantly with COS, letrozole in a dose of 5 mg and tamoxifen in a dose of 20 mg were given orally on a daily basis. The trigger was performed with 0.2 mg of triptorelin, in the presence of follicles ≥ 19 mm. Oocyte retrieval was scheduled 35-36 hours after triptorelin injection. Our main outcome measures were the number of oocytes collected and number of oocytes vitrified, the length of ovarian stimulation, total dose of gonadotropins administered, and levels of estradiol on the day of the trigger. Results: The mean age of patients was 30.43 ±4.25 years. Nineteen women commenced COS in the luteal phase, eleven in the early follicular phase and ten in the late follicular phase. The mean number of collected oocytes was 11.78 ±9.12 and the mean number of vitrified oocytes was 9.72 ±7.36. The mean duration of COS was 10.03 ±1.33 days. The mean estradiol concentrations on the triggering day was 623.10 ±441.27, and the mean dose of gonadotropins administered was 2540 ±713.10. Conclusions: The authors suggest that the protocol is efficient and may be a safe option for oocyte vitrification in these patients.
Keywords: Breast cancer; Fertility preservation; Letrozole; Ovarian stimulation; Tamoxifen